Detection of persistent Plasmodium spp. infections in Ugandan children after artemether-lumefantrine treatment. Issue 14 (16th May 2014) - BETSON, MARTHA; SOUSA-FIGUEIREDO, JOSÉ C.; ATUHAIRE, AARON; ARINAITWE, MOSES; ADRIKO, MOSES; MWESIGWA, GERALD; NABONGE, JUMA; KABATEREINE, NARCIS B.; SUTHERLAND, COLIN J.; STOTHARD, J. RUSSELL
SUMMARY: During a longitudinal study investigating the dynamics of malaria in Ugandan lakeshore communities, a consistently high malaria prevalence was observed in young children despite regular treatment. To explore the short-term performance of artemether-lumefantrine (AL), a pilot investigation into parasite carriage after treatment(s) was conducted in Bukoba village. A total of 163 children (aged 2–7 years) with a positive blood film and rapid antigen test were treated with AL; only 8·7% of these had elevated axillary temperatures. On day 7 and then on day 17, 40 children (26·3%) and 33 (22·3%) were positive by microscopy, respectively. Real-time PCR analysis demonstrated that multi-species Plasmodium infections were common at baseline, with 41·1% of children positive for Plasmodium falciparum / Plasmodium malariae, 9·2% for P. falciparum / Plasmodium ovale spp. and 8·0% for all three species. Moreover, on day 17, 39·9% of children infected with falciparum malaria at baseline were again positive for the same species, and 9·2% of those infected with P. malariae at baseline were positive for P. malariae . Here, chronic multi-species malaria infections persisted in children after AL treatment(s). Better point-of-care diagnostics for non-falciparum infections are needed, as well as further investigation of AL performance in asymptomatic individuals.